A LEGAL ANALYSIS ON IMPLICATIONS OF AUDIO JOURNALISM AND PODCASTING ON PRINT MEDIA JOURNALISTS - Mano, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Journalists play a vital role in having a country with well-informed citizen. They are the gatekeeper of what qualifies to be heard in the public sphere. The time has come to re-examine the gatekeeper theory because of the emergence of the innovative new media practices. The journalist role is transforming by innovations of various advanced digital technologies. Audio journalism and podcasting techniques also transforming the industry by its innovative way of conveying information. This paper focuses on the legal analysis on implications of Audio journalism and Podcasting on working journalists especially print media journalists from Indian Labour Law Perspective.